Supporting Culturally Responsive Assessment Practices With Preschoolers: Guidance From Methods in the Jamaican Context. - Washington, Karla N.; Wright Karem, Rachel; Kokotek, Leslie E.; León, Michelle (Journal of Speech, Language & Hearing Research, 2023)
Purpose: There is a shortage of available methods to accurately inform the developmental status of children whose cultural and linguistic backgrounds vary from the mainstream. The purpose of this review article was to describe different approaches used to support the accurate characterization of speech, language, and functional communication in children speaking Jamaican Creole and English, an understudied paradigm in the speech pathology research. Method: Approaches used across four previously published studies in the Jamaican Creole Language Project are described. Participants included 3- to 6-year-old Jamaican children (n = 98-262) and adults (n = 15-33). Studies I and II described validation efforts about children's functional communication using the Intelligibility in Context Scale (ICS; speech) and the Focus on the Outcomes of Communication Under Six (FOCUS; speech and language). Study III described efforts to accurately characterize difference and disorder in children's expressive grammar using adapted scoring, along with adult models to contextualize child responses. Last, Study IV applied acoustic duration (e.g., whole word) and an adapted scoring protocol to inform variation in speech sound productions in the Jamaican context where a post-Creole continuum exists. Results: Studies I and II offered promising psychometric evidence about the utility of the ICS and the FOCUS. Study III revealed strong sensitivity and specificity in classifying difference and disorder using adult models. Last, in Study IV, linguistically informed acoustic analyses and an adapted protocol captured variation in speech productions better than a standard approach. Conclusions: Applying culturally responsive methods can enhance the accurate characterization of speech, language, and functional communication in Jamaican children. The innovative methods used offer a model approach that could be applied to other linguistic contexts where a mismatch exists between speech-language pathologists and their clientele. Presentation Video: https://doi.org/10.23641/asha.23929461